HUBUNGAN TINGKAT PENGETAHUAN, SIKAP DAN PERSEPSI MASYARAKAT DENGAN TINDAKAN VAKSINASI COVID-19 DI KOTA PADANG - Mailani, Fitri; Ariany Maisa, Esthika; Zikri, Rahmi (Universitas Udayana, 2023)
COVID-19 Vaccination is the most effective way to prevent and retard the spread of COVID-19. However, there are still many people who are unwilling to COVID- 19 vaccination. as evidenced by the provide of West Sumatra,it is provide position of sumatra province witch is 7th lowest province to the COVID-19 vaccine in Indonesia. The low coverage of COVID-19 vaccine knowledge is influenced by several factors, including level of knowledge, attitudes and perceptions. The purpose of this study was to determine the correlation between the level of knowledge, attitudes and public perceptions toward the COVID-19 vaccination measures in Kalumbuk Village, Padang City in 2021. The research design used cross sectional study method with a sample of 182 respondents using accidental sampling technique, with community respondents represented by each family head Data processing was done by computerization and analysis using the Chi-Square method. The results of this study show that regarding COVID-19 vaccination in Kalumbuk Village, Padang City, most have a sufficient level of knowledge (61%), positive attitudes (61.5%), positive perceptions (62,6%) and good measuring (53,3%). There is a significant correlation between the level of knowledge and measures of COVID-19 vaccination (p=0,000), attitudes and measures of COVID-19 vaccination (p=0,007), perceptions and measures of COVID-19 vaccination (p=0,000). There is a corellation between the level of knowledge, attitudes and perceptions of the community toward the COVID-19 vaccination measures in Kalumbuk Village, Padang City in 2021. This research can be input for nursing service institutions to increase the knowledge of people who have sufficient and less knowledge levels by providing counseling by media information and education related to COVID-19 vaccination.